The Evolution of Mediation in International Conflicts from 1940s to 2020s - M. M. Lebedeva (Vestnik MGIMO-Universiteta, 2024)
The article analyzes the evolution of international mediation from the middle of the 20th century to the present day. How do changes in international environment influence mediation and research on it? The paper’s hypothesis is that the transformation of international order and political organization of the world, the dynamics of (de)globalization and changes in the nature of international conflict determine the specifics of international mediation and shape the relevant research. Over the last 80 years international mediation evolved through three stages. During the first stage, shaped by the cold war, conflicts were mostly of interstate nature and were settled by states and international organizations. Meanwhile, the growing activity of non-state actors led to the emergence of mediation via “track II diplomacy”. At this stage, the study of international mediation becomes an established research area. The second stage, since the end of 1980s to the beginning of the 21st century, witnessed a rapid progress in the settlement of many protracted regional conflicts, aided by the mediation efforts of the USSR and the United States. In Russia, research on international mediation, previously fragmentary and legalistic, developed into a separate subfield of international studies. During the third stage, in the 21st century, the political organization of the world has been undergoing a turbulent transformation at all the three levels: Westphalian system, the system of interstate relations, and political systems of individual states. The all-encompassing nature of this change increases conflict potential and changes the nature of international conflicts, which become multidimensional and involve a variety of actors. Responding to the demand for managing complex conflicts, new trends in mediation emerge, such as the growth in mediation attempts by developing nations, engagement of peacekeeping missions in mediation, the use of digital technologies for mediation purposes. At the same time, the erosion of the old political organization of the world triggers the rise in identity-based conflicts that involve disagreement over values. As parties to such conflicts are less likely to seek interestbased compromises, the likelihood of successful mediation decreases.